Use of rivers' water, inadequate hygiene, and sanitation as exposure of internally displaced persons (IDPs) to urogenital schistosomiasis and soil-transmitted helminthiasis in Jalingo Local Government Area (LGA), Taraba State, Nigeria. (21st October 2022) - Binga, Wama Emmanuel; Houmsou, Robert Soumay; Garba, Liatu Columbus; Amuta, Elizabeth Une; Santaya, Kela Larit
Abstract: Water- and soil-transmitted helminthiasis in relation to socio-demographic status and risk factors of internally displaced persons in Jalingo Local Government Area (LGA) were determined. The nutritional status was also studied among infected individuals. Urine filtration and Kato-Katz techniques were used to examine urine and faecal samples, respectively. Urogenital schistosomiasis infection was found at a moderate level of 52 (17.6%), whereas ascariasis and hookworm infection were 48 (16.3%) and 8 (2.7%), respectively. Participants in Jauro Gbadi camp as well as the age group (41–50) years significantly had the highest infection with hookworm, 8 (8.2%) ( χ 2 = 16.70; p = 0.000) and 2 (11.7%)( χ 2 = 17.59, p = 0.003), respectively. Farmers were significantly infected with urogenital schistosomiasis (20.1%) ( χ 2 = 14.03; p = 0.043). Fishing in rivers exposed individuals to urogenital schistosomiasis with an adjusted odds ratio (aOR) = 8.60 (95% CI: 0.86–85.52; p = 0.046). The lack of hygienic measures exposed individuals who 'don't wash their hands before eating' to soil-transmitted helminthiasis with an aOR = 4.13 (95% CI: 0.77–21.99; p = 0.045). In sanitation, individuals who 'don't use pit latrines and do use the bush for defaecating' were exposed to soil-transmitted helminthiasis with an aOR = 2.14 (95% CI: 1.30–3.52; p = 0.002). Farmers were infected with urogenital schistosomiasis. Participants in the Jauro Gbadi camp and individuals within the age group (41–50) years had high hookworm infection. Use of river water, inappropriate hygiene, and sanitation exposed individuals to infection. HIGHLIGHTS: A first investigative study of urogenital schistosomiasis and soil-transmitted helminthiasis among internally displaced persons using river and pond water in Jalingo Local Government Area, Taraba State, Nigeria. Fishing and bathing activities in rivers exposed internally displaced persons to urogenital schistosomiasis. Unwashed hands before eating, and after defaecation as well as defaecating in the open exposed internally displaced persons to soil-transmitted helminthiasis.